Distribution of Ia-like molecules on the surface of normal and leukemic human cells. - Schlossman, S F (1976)
Antiserum to a glycoprotein antigen complex of 23,000 and 30,000 dalton subunits (p23,30), isolated and purified from a human lymphoblastoid B cell line, was shown to be highly specific for human bursal-equivalent-processed (B) cells, reactive with 15-20% of human Null cells, but completely unreactive with human thymus-processed (T) cells. The p23,30 antigen is widely distributed on chronic lymphatic leukemic cells, 85% of acute lymphatic leukemic cells, all acute myelogenous leukemic cells, but not on chronic myelogenous leukemic cells. A rabbit antiserum specific for normal human thymocytes has also been prepared; it is reactive only with precisely that subset of acute lymphatic leukemic cells (15%) whose members do not have p23,30 on their surfaces.